“I Glanced into the Nether-World.” Some Remarks on the Tradition of Conversations with the Dead in the Writings of Cyprian Norwid - Seweryn, Agata (Colloquia Litteraria, 2018)
The study focuses on the tradition of the conversations among the dead in Cyprian Norwid’s works, especially in the poem Vendôme. While noting Norwid’s transformations of classical and classicist conventions, the author points to the mannerist and baroque contexts, and on the other hand, to ekphrastic qualities of Norwid’s literary imagination.